Simple Wireless Nurse Call on Distance Measurement - Kartika, Wisnu; Santoso, Irvan; Supriyadi, Kuat (Universitas Muhammadiyah Yogyakarta, 2021)
On this era, many patient go to the hospital and the clinic because the service is better than yesterday. If there are patient suffer a sickness and on the patient bed so the patient will call the nurse using a bell to call the nurse on the treatment room on the hospital. The previous research uses cable to connect the nurse room with the patient room. In this research we proposed a new scheme that is wireless nurse call. The wireless nurse call will minimize the cable. This research module using Arduino. There are consist of transmitter and receiver module. The system consists of the software and the hardware. There are one master transmitter module and four receiver module. The receiver module is tested on several place and several barrier.Â The visualization can be displayed on the PC (Personal Computer) or Laptop using Microsoft Visual C# software. The visualization is included the four room notification with display and sound. From the research, this module can work well. From the research, we conclude that the module can work and can over the barrier and several far away from the master module.Â